2014
DOI: 10.7550/rmb.43848
|View full text |Cite
|
Sign up to set email alerts
|

Corales pétreos, equinodermos y peces asociados a comunidades y arrecifes coralinos del Parque Nacional Huatulco, Pacífico sur mexicano

Abstract: Resumen. Producto de la revisión de literatura científica especializada, visitas a colecciones de referencia y trabajo de campo, se presenta el listado de corales pétreos (10 especies), equinodermos (32 especies) y peces (150 especies) que habitan el Parque Nacional Huatulco (PNH). Las 192 especies aquí registradas representan un incremento de ~ 66.9% respecto a estudios previos. En cuanto a otras áreas naturales protegidas (ANP) en México, el PNH alberga una riqueza de especies mayor con relación a las ANP lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 35 publications
1
13
0
21
Order By: Relevance
“…However, the particular effects and their magnitude depend on each individual species, and also vary with the stage of the life cycle and the duration of exposure [ Price et al ., ; Tambutté et al ., ]. Along with other species, the coral Pocillopora damicornis prospers in the GoT and is regarded as the most abundant coral species in the region [ López‐Pérez et al ., ]. It has been reported that pH values of 7.4 and Ω Ar levels of 1.1, such as those found in this work, produce an overregulation of genes encoding for the proteins involved in calcification, while a pH of 7.2 (RR = 0.68) decreases their regulation [ Vidal‐Dupiol et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the particular effects and their magnitude depend on each individual species, and also vary with the stage of the life cycle and the duration of exposure [ Price et al ., ; Tambutté et al ., ]. Along with other species, the coral Pocillopora damicornis prospers in the GoT and is regarded as the most abundant coral species in the region [ López‐Pérez et al ., ]. It has been reported that pH values of 7.4 and Ω Ar levels of 1.1, such as those found in this work, produce an overregulation of genes encoding for the proteins involved in calcification, while a pH of 7.2 (RR = 0.68) decreases their regulation [ Vidal‐Dupiol et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Ecologically important coral species such as Pocillopora damicornis , P. meandrina , and Porites panamensis live in the coastal areas of the GoT [ López‐Pérez et al ., ]. Aragonite saturation state variability may affect corals and other calcifying species such as coccolithophorids and foraminifera [ Müller et al ., ; Rixen et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Ixtapa, Aguilar-Medrano and Calderón-Aguilera 2015) and Oaxaca (e.g. Huatulco, López-Pérez et al 2014). However, the species richness recorded in Carrizales was lower than that reported by Reyes-Bonilla et al (2013), since P. stellata and P. contigua, which are of low cover and frequency, were not observed.…”
Section: Discussionmentioning
confidence: 42%
“…The dissimilarities found at regional scale support the findings of previous studies (Aguilar-Medrano and Calderón-Aguilera 2015). Specifically, P. verrucosa is the most abundant coral in the northern portion of the Mexican Pacific (Reyes-Bonilla 2003), while P. damicornis is the main constituent of coral ecosystems in Oaxaca, in the southernmost region of the Mexican Pacific (López-Pérez et al 2014) and in Central America (Glynn and Ault 2000).…”
Section: Discussionmentioning
confidence: 99%
“…4, 5); ello se debe a que en los pixeles se aprecian cambios mínimos de temperatura (entre -0.73 y +1.23 °C) y de Ω aragonita (entre -1.3 y +0.13 unidades) para el año 2050. En particular, en lo que concierne a la parte sur del golfo de California, el panorama presentado en este estudio está en línea con estudios anteriores que apoyan la idea de que esta zona estará en relativamente bajo estrés térmico porque está más influenciada por la corriente de California en invierno y primavera (Kessler, 2006;López-Pérez et al, 2014).…”
Section: Discussionunclassified